LA BELLEZA DEL CUERPO FEMENINO - Alvarado Steller, Valerie (2012)
The present article contains a bibliographical revision which objective is to investigate the concept of beauty and corporal image that the women have and have had through history. Firstly, a brief review of how the feminine body has been changing in relation to the conception of beauty is presented, later on, the factors that has determined this change are presented so as the impact on the corporal image of the woman itself. That perception is often influenced by the media, the context and the society. Finally, it will be discussed on the subject in relation to the normality that all society proposes.